Collagen proton fraction from ultrashort echo time magnetization transfer (UTE‐MT) MRI modelling correlates significantly with cortical bone porosity measured with micro‐computed tomography (μCT). (14th December 2018) - Jerban, Saeed; Ma, Yajun; Wan, Lidi; Searleman, Adam C.; Jang, Hyungseok; Sah, Robert L.; Chang, Eric Y.; Du, Jiang
Abstract : Intracortical bone porosity is a key microstructural parameter that determines bone mechanical properties. While clinical MRI visualizes the cortical bone with a signal void, ultrashort echo time (UTE) MRI can acquire high signal from cortical bone, thus enabling quantitative assessments. Magnetization transfer (MT) imaging combined with UTE‐MRI can indirectly assess protons in the bone collagenous matrix, which are inversely related to porosity. This study aimed to examine UTE‐MT MRI techniques to evaluate intracortical bone porosity. Eighteen human cortical bone specimens from the tibial and fibular midshafts were scanned using UTE‐MT sequences on a clinical 3 T MRI scanner and on a high‐resolution micro‐computed tomography (μCT) scanner. A series of MT pulse saturation powers (500°, 1000°, 1500°) and frequency offsets (2, 5, 10, 20, 50 kHz) were used to measure the macromolecular fraction (MMF) and macromolecular T 2 ( T 2MM ) using a two‐pool MT model. The measurements were made on 136 different regions of interest (ROIs). ROIs were selected at three cortical bone layers (from endosteum to periosteum) and four anatomical sites (anterior, mid‐medial, mid‐lateral, and posterior) to provide a wide range of porosity. MMF showed moderate to strong correlations with intracortical bone porosity ( R = −0.67 to −0.73, p < 0.01) and bone mineral density (BMD) ( R = +0.46 to +0.70, p < 0.01). Comparing the average MMF between cortical bone layers revealed a significant increase from the endosteum towards the periosteum. Such a pattern was in agreement with porosity reduction and BMD increase towards the periosteum. These results suggest that the two‐pool UTE‐MT technique can potentially serve as a novel and accurate tool to assess intracortical bone porosity. Abstract : UTE‐MT MRI techniques was highlighted as a useful method to assess intracortical bone porosity that was validated ex vivo on human tibiae and fibulae midshafts. Macromolecular proton fraction (MMF), obtained from MT modeling, as a quantification for collagenous matrix content, showed strong correlations with bone porosity and BMD from µCT. The correlations were consistently high for both tibial and fibular bone specimens, insensitive to the type of long bone.